(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article presents how to enhance the teaching of technical techniques in wrestling. The method of modeling the teaching of technical actions in wrestling practice classes is developed. Questionnaire of coaches on the use of the method of modeling the training process is conducted.